Flow injection determination of sodium, potassium, calcium, and magnesium in beer by flame emission and atomic absorption spectrometry - Fernandes, Sílvia M. V. (2011)
Flow injection systems for the determination of sodium and potassium, by flame emission photometry, and calcium and magnesium, by atomic absorption spectrometry, in beer are described. The samples were directly injected in the flow system where automatic dilution occurred, and reagent addition using the merging zones technique was performed. Lanthanum(III) consumption was reduced in about 20-80-fold compared to conventional manual atomic absorption determinations. Sampling rates of 120-200 determinations/h were achieved. The results were in agreement with the reference procedures (relative deviations below 3.8%) and present good reproducibility (relative standard deviations lower than 1.6% for 10 consecutive measurements).